Achieving stable canal conditions following remodeling: the case study of Bareji Distributary, Mirpurkhas - Lashari, Bakhshal K.; Murray-Rust, Hammond; Talpur, Mashooq (International Water Management Institute, 2000)
This study looks into the unsatisfactory indications canal and structure dimensions and levels of water distribution equity. These changes result in conditions that do not permit regime to be established and result in high variation between the head and the tail of the distribution.